2007
DOI: 10.1016/j.annemergmed.2007.01.017
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring and Forecasting Emergency Department Crowding in Real Time

Abstract: The EDWIN, the NEDOCS, and the Work Score monitor current ED crowding with high discriminatory power, although none of them exceeded the performance of occupancy level across the range of operating points. None of the measures provided substantial advance warning before crowding at low rates of false alarms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 62 publications
1
99
0
3
Order By: Relevance
“…Recent research shows that ED occupancy predicts overcrowding as well as these workload measures [Hoot et al 2007] and correlates well with the staff's perception of overcrowding [McCarthy et al 2008]. …”
Section: Threshold Policiesmentioning
confidence: 99%
“…Recent research shows that ED occupancy predicts overcrowding as well as these workload measures [Hoot et al 2007] and correlates well with the staff's perception of overcrowding [McCarthy et al 2008]. …”
Section: Threshold Policiesmentioning
confidence: 99%
“…The recent literature discusses numerous methods ranging from multivariable regression analysis to nonlinear techniques, discrete event simulation, and neural networks. 11,19,27,[30][31][32][33][34][35] As reported, all of these approaches function reasonably well in providing short-term forecasts of various lengths for a variety of ED operational characteristics. However, many of these models may use proprietary software and often require input of many operational variables, some from outside of the ED, to generate their forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the measure of ED bed occupancy performs no worse than more complex scores such as EDWIN in identifying ED crowding. [25][26][27] Another important consideration in the development of this study was how to interpret the ED bed occupancy metric: should it be treated as a continuous metric or should a threshold approach be used, in which either an ED is crowded or it is not? While some important ED performance metrics may become abnormal at an easily discerned threshold occupancy level, a crowding metric that can supply a universally applicable threshold of ''this ED is now crowded'' remains to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Other ED studies focused on analyzing nurse and physician staffing, patient length of stay (LOS), quality, and crowding. [16][17][18] This study is distinct in examining the effects of improving patient throughput (i.e., reducing dwell time) on temporal patterns of crowding at both an urban and community ED.…”
Section: Introductionmentioning
confidence: 99%